DOVE, EDUKASI PASAR DENGAN HARAPAN - Setiadi Umar (Bina Ekonomi, 2006)
Many companies and management authors have recognized the importance of product innovation. They call it, "first mover advantage". However this product innovation is not without risk. In reality many product innovations have failed and busted. Many failed because of a single reason: low level of market acceptance. To make the matter worse, the product that finally succeeded in gaining market acceptance only to be taken over, or to be bought, or to be replaced because they could not stand from the competition, especially from those multinational companies that have better resources and better staffs. Up until now, only few new product categories that actually enjoyed what they called first mover advantage and all of them have a similarity: they are the first that dominated the market or they have a good patent protection. Forming a market itself is clearly challenging. Dominating the market presents another challenge. This literature is trying to give an insight about how primary demand is formed, by observing Unilever, in her effort in making a new market for one of her products, Dove. We observe how Unilever through Dove is trying to build a new product category inside her consumer mind and how Unilever is trying to educate their market by saying that clean is slippery not arid in the society that have a contrary habit. We hope that this literature could prove helpful in future work on forming a primary demand in new product category and on launching new product.